Serum growth hormone level in newborn with intra - uterine growth restriction - Gamal Ahmed Ismail Elghazawi; Abdelrahman Ahmed Abdelrazek; Ayman Abdelrahman Ahmed Elbadawy; Nelly Nader Abdeldayem Abulata (Cairo : Gamal Ahmed Ismail Elghazawi, 2010)
IUGR refers to a condition in which a fetus is unable to achieve its genetically determined potential size . This definition intentionally excludes fetuses that are small for gestational age (SGA) but are not pathologically small . IUGR results when a problem or abnormality prevents cells and tissues from growing or causes cell to decrease in size
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Growth hormone; Intrauterine Growth Restriction; Out come of IUGR